Pilgrim interaction with services provided by the general presidency of Alharamain affairs - FARHI, F; MOHAMED, M.M.A (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study aimed at identifying the interaction of pilgrims with the services provided by the General Presidency of The Affairs of the Two Holy Mosques through "Facebook". The descriptive method was used as a data collection tool. The field sample consisted of 200 individuals spalled from the two pages, ’Ministry of Hajj’ and ‘The Grand Mosque’. Findings show that there are statistically significant differences between the forms of interaction of the respondents with the services provided by the General Presidency for the Two Holy Places on the pages of the Ministry of Hajj and the Grand Mosque, and in the direction.